Effect of ethanol concentration in water coagulation bath on pore geometry of PVDF membrane for Membrane Gas Absorption application in CO 2 removal - Abdul Latif, Ahmad, Prof. Dr.; W. K., W. Ramli; Fernando, Weeramundage James Noel; Wan Ramli, Wan Daud, Prof. Ir. Haji Dr. (Elsevier B.V., 2012)
Link to publisher's homepage at http://www.elsevier.com/